A clinician's guide to managing atopic dermatitis in dogs. Issue 8 (2nd October 2020) - Barnard, Natalie
Abstract : Background: Atopic dermatitis is a complex condition in dogs that requires lifelong management. As such, veterinarians and owners must work together to manage these difficult cases to get the best clinical outcome for the animal. Aim of the article: This article provides a guide to the different management options available for dealing with cases of atopic dermatitis in dogs, and things to consider when deciding on the best course of action.